Whole-Exome Sequencing Identifies Damaging de novo Variants in Anencephalic Cases - Wang, Linlin; Ren, Aiguo; Tian, Tian; Li, Nan; Cao, Xuanye; Zhang, Peng; Jin, Lei; Li, Zhiwen; Shen, Yan; Zhang, Bo; Finnell, Richard H.; Lei, Yunping (Frontiers in Neuroscience, 2019)
Background: Anencephaly is a lethal neural tube defect (NTD). Although variants in several genes have been implicated in the development of anencephaly, a more complete picture of variants in the genome, especially de novo variants, remains unresolved. We aim to identify de novo variants (DNVs) that play an important role in the development of anencephaly by performing whole-exome DNA sequencing (WES) of proband-parent trios. Results: A total of 13 DNVs were identified in 8 anencephaly trios by WES, including two loss of function (LoF) variants detected in pLI >0.9 genes (SPHKAP, c.2629_2633del and NCOR1, p.Y1907X). Damaging DNVs were identified in 61.5% (8/13) of the anencephalic cases. Independent validation was conducted in an additional 502 NTD cases. Gene inactivation using targeted morpholino antisense oligomers and rescue assays were conducted in zebrafish, and transfection expression in HEK293T cells. Four DNVs in four cases were identified and predicted to alter protein function, including p.R328Q in WD repeat domain phosphoinositide-interacting 1 (WIPI1). Three variants, p.G313R, p.T418M, and p.L406P, in the WIPI1 gene were identified from the independent replication cohort consisting of 502 cases. Functional analysis suggested that the wipi1 p.L406P and p.R328Q variants most likely displayed loss-of-function effects during embryonic development. Conclusion: De novo damaging variants are the main culprit for majority of anencephalic cases. Missense variants in WIPI1 may play a role in the genetic etiology of anencephaly, and LoF variants in SPHKAP and NCOR1 may also contribute to anencephaly. These findings add to our existing understanding of the genetic mechanisms of NTD formation.